2009
DOI: 10.1007/s11926-009-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal manifestations of the antiphospholipid syndrome

Abstract: The antiphospholipid syndrome is characterized by recurrent arterial and venous thromboses and pregnancy morbidity in association with antiphospholipid antibodies. Recurrent thrombotic events are associated with significant morbidity and mortality. Renal involvement encompasses the whole renal vasculature and may lead to proteinuria, renal impairment, hypertension, and end-stage renal failure. Renal involvement is especially difficult to distinguish from glomerulonephritis when the antiphospholipid syndrome de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Hypertension is also common in APS, occurring in 28% of patients in one cohort (31). The majority of these patients do not have primary renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is also common in APS, occurring in 28% of patients in one cohort (31). The majority of these patients do not have primary renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, APS is associated with a range of renal manifestations including renal artery stenosis, cortical ischaemia, thrombotic microangiopathy and thrombosis of the renal vein or inferior vena cava. Hypertension with APS therefore needs careful investigation and renal ultrasound, glomerular filtration rate, dimercaptosuccinic acid (DMSA) scans and imaging of the renal arteries and veins should be considered (31).…”
Section: Discussionmentioning
confidence: 99%
“…Though TMA can occur under various other conditions,[11] the presence of TMA in the setting of suspected APS is considered characteristic of APS nephropathy. [12] Histologically, renal biopsy shows focal or diffuse microangiopathic changes with fresh and old recanalized thrombi. The glomerular capillaries are occluded by fibrin thrombi and proliferating endothelial cells bulging into the vascular lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Once patients are established on warfarin, aspirin does not offer any added advantage. [12] Methylprednisolone, anticoagulants, cyclophosphamide, and plasma exchange have been used in various combinations to achieve renal recovery. [15–17]…”
Section: Discussionmentioning
confidence: 99%
“…Thrombotic microangiopathy, which is common in catastrophic APS and/or transplant rejection, is the most characteristic lesion of APS nephropathy; the pathologic changes may be similar to other TMAs, e.g., HUS, TTP, and preeclampsia. In addition, aPL-nephropathy patients can develop chronic cortical ischemia/infarction (arteriosclerosis, arteriolosclerosis, arterial fibrous intimal hyperplasia, glomerular ischemia, interstitial fibrosis, tubular thyroidization, tubular atrophy, and/or organized thrombi with/without recanalization) [ 1 , 27 , 28 ]. Recently, it has been shown that in APS patients these vascular renal lesions are associated with the activation of the mammalian target of rapamycin pathway [ 29 ].…”
Section: Antiphospholipid Syndromementioning
confidence: 99%